If it's not what You are looking for type in the equation solver your own equation and let us solve it.
35=5(x+8)+3
We move all terms to the left:
35-(5(x+8)+3)=0
We calculate terms in parentheses: -(5(x+8)+3), so:We get rid of parentheses
5(x+8)+3
We multiply parentheses
5x+40+3
We add all the numbers together, and all the variables
5x+43
Back to the equation:
-(5x+43)
-5x-43+35=0
We add all the numbers together, and all the variables
-5x-8=0
We move all terms containing x to the left, all other terms to the right
-5x=8
x=8/-5
x=-1+3/5
| 3y-12y^2=0 | | 16x+6x+26=180 | | x÷3=13 | | 5x^2-28x-12=0. | | 4(3r-2)=4(2r-3) | | 71=x | | 2(x+24)=8x+2 | | 129=1/4t | | 8z+-4z=-16 | | 13–5y=8y | | 114=x | | 5x^2-2x=x^2=10x | | -4v+-7=-5 | | 3g+5=8g+7+12g | | 5x^2-3x=x^2=10x | | 5x^2-3x=x^2=0 | | 2j+-5=-1 | | 3y+2-5y=22 | | (8+2)x(1x1)x5=5 | | 12(2x-5)=108 | | 5(y+2)=-15 | | (x*15)/100=125 | | x2-2.5x=0 | | -12x+144=-9+(-63x) | | 5(5f=2)=5(3f+4) | | 1/8-x=-10 | | 3y+10=32 | | 5(5f=2)5(3f+4) | | 3(7n-4)-9n=-7(4n-2)+15n-1 | | 1x+26=1x-8 | | 6(4+2r)=3(5r+4) | | 2x-(1/6)=3 |